Adaptive and Robust Control for Energy Efficiency Enhancement of a Solar-powered Desalination System⁎This work has been supported by the King Abdullah University of Science and Technology (KAUST), Base Research Fund (BAS/1/1627-01-01) to Taous Meriem Laleg. Issue 2 (2020) - Alharbi, Mohammad; Aljehani, Fahad; N'Doye, Ibrahima; Laleg-Kirati, Taous-Meriem
Abstract: In this paper, an adaptive control strategy is proposed to enhance the energy production efficiency under environmental changes. The control objective is to force the outlet temperature of a solar thermal collector fluid to track the desired reference temperature regardless of the solar irradiance variations. An adaptive nonlinear control that combines an inner loop feedback control and an outer loop model-free control strategy is proposed to ensure asymptotic convergence of the tracking error. The proposed adaptive control strategy is applied to an approximate bilinear model derived from the heat transfer equation. Numerical simulations are presented to illustrate the performance of the control strategy in terms of tracking accuracy and settling time. Furthermore, the improvement in energy production is highlighted through a powering thermal membrane distillation based desalination in increasing water production.